Clinical performance of the Sofia™ Influenza A + B FIA in adult patients with influenza-like illness - Noh, Ji Yun (Diagn Microbiol Infect Dis, 2015)
The Sofia™ Influenza A + B FIA demonstrated 74.0% sensitivity and 95.4% specificity for influenza A in patients with influenza-like illness in 2012–2013 season. It yielded higher sensitivity than SD Bioline Influenza Ag A/B/A(H1N1/2009) (54.1%) for influenza A (P < 0.01). The Sofia™ Influenza A + B FIA might be useful for rapid diagnosis of influenza.